Observations on the Behavioral Responses of Bowhead Whales (Balaena mysticetus) to Active Geophysical Vessels in the Alaskan Beaufort Sea - Ljungblad, Donald K.; Würsig, Bernd; Swartz, Steven L.; Keene, James M. (ARCTIC, 1988)
The responses of bowhead whales to controlled approaches by geophysical vessels producing airgun blasts were observed during the course of four field experiments conducted in the Alaskan Beaufort Sea in September 1984. Behavioral responses included shorter surfacing and dive times, fewer blows per surfacing, longer blow intervals and subtle to overt changes in surface behaviors. Subtle behavioral responses occurred at 3.5 and 8.2 km with received airgun noise levels of 142 and 157 dB respectively (all levels in dB re 1 micro Pa). Partial avoidance (i.e., some whales leaving the observation area while others remained) occurred at ranges of 3.5 and 7.6 km, with sound levels of 142 and 158 dB respectively. Total avoidance (i.e., all whales leaving the observation area) occurred at 1.3, 7.2, 3.5 and 2.9 km, with corresponding sound levels of 152, 165, 178 and 165 dB. The similarities among experiments reported here support the conclusion that short-term behavioral changes occur when bowhead whales are exposed to airgum blasts from approaching geophysical vessels at ranges <10 km. These disturbance efforts wane within one hour after a disturbance; long-term effects on social, behavioral or physiologic parameters are not known at this time.Key words: bowhead whale, Balaena mysticerus, geophysical vessel, bioacoustics, airguns Mots clés: baleine franche, Balaena mysticetus, navire de prospection géophysique, bioacoustique, canons à air